Characterizing hydro-mechanical behaviours of compacted subgrade soils considering effects of freeze-thaw cycles. (September 2020) - Ding, Lu-qiang; Han, Zhong; Zou, Wei-lie; Wang, Xie-qun
Highlights: FT cycles reduce soils' water retention capacity and moisture sensitivity. Relationships of M R to q u, E 1% and S u1% are not sensitive to FT cycles. M R reduced most significantly at a w level wet of w opt after FT cycles. Empirical equations were proposed to predict M R considering FT influences. Abstract: This paper presents a series of experimental studies for evaluating the effects of closed-system freeze–thaw (FT) cycles on the hydro-mechanical behaviours of two subgrade soils (a low plastic lean clay, SS and a lean clay with higher plasticity, HC). Investigated hydro-mechanical behaviours include the soil–water characteristic curve (SWCC) obtained from the filter paper method, resilient modulus ( M R ) determined from cyclic triaxial tests, unconfined compression strength ( q u ) and reloading tangent modulus ( E 1% ) and stress ( S u1% ) at 1% strain measured from unconfined compression tests, with emphasis on the SWCC and M R . Specimens compacted at the maximum dry density ( ρ dmax ) and optimum moisture content ( w opt ) were firstly subjected to multiple FT cycles (number of FT cycles NFT = 0, 1, 3, 6 and 10) and then dried or wetted to different moisture contents before determining hydro-mechanical behaviours. Experimental results revealed that (i) FT cycles reduce the magnitude of volumetric strain upon moisture variation for the HC but have little impact on the SS; (ii) FT cycles reduce the water retention capacity of both soils. For each soil, the void ratio ( e )-moisture content ( w )-suction ( s ) relationships after different FT cycles are possibly distributed on a unique surface; (iii) Reductions in the mechanical properties (i.e. M R, q u, E 1% and S u1% ) are more significant at NFT = 1 and vary with the post-FT cycle moisture content. Reductions in the M R are most serious at a threshold w level on the wet side of w opt ; (iv) FT cycles reduce the sensitivity of the mechanical properties to moisture content for the HC but exert minor influence on that of the SS; (v) Relationships of the M R to the q u, E 1% and S u1% are not influenced by the NFT and moisture content for both soils. They are non-linear and can be well described by quadratic polynomials. Soils with higher plasticity such as the HC is, in general, more vulnerable to effects of closed-system FT cycles at w opt than low plastic soils such as the SS.